ANALISIS RENDAHNYA IMPLEMENTASI PENGGUNAAN ALAT PELINDUNG DIRI (APD) DI KMP. TITIAN NUSANTARA - Findhea Tosy Margareta; I Kadek Laju; Bayu Yudho Baskoro; Syafni Yelvi Siska; Derma W.S (STKIP Subang, 2026)
Occupational Safety and Health (OSH) is a crucial aspect in ship operations, particularly on deck where the risk of work accidents is relatively high. The use of Personal Protective Equipment (PPE) by deck crew is essential to prevent injuries and maintain safe working conditions. This study aims to identify factors causing the low implementation of PPE usage, its impacts, and the efforts required to improve compliance on board KMP. Titian Nusantara. This research used a descriptive qualitative method conducted during the sea practice period on board KMP. Titian Nusantara. Primary data were obtained through observation and semi-structured interviews with deck crew, Bosun, and Chief Officer. Secondary data were collected from ship documents, safety procedures, and relevant literature. Data analysis was carried out using Fish Bone Analysis to identify the root causes of low PPE implementation. The results show that low PPE usage is influenced by limited understanding, work habits, low motivation, inconsistent work methods, inadequate PPE condition, hazardous work environment, and lack of supervision. Improvement efforts include safety training, stronger supervision, procedural improvements, and proper provision and maintenance of PPE.